9p21.3 Coronary Artery Disease Locus Identifies Patients With Treatment Benefit From Bariatric Surgery in the Nonrandomized Prospective Controlled Swedish Obese Subjects Study. (October 2020) - Jacobson, Peter; Peltonen, Markku; Svensson, Per-Arne; Taube, Magdalena; Andersson-Assarsson, Johanna C.; Sjoholm, Kajsa; Bouchard, Claude; Carlsson, Björn; Carlsson, Lena M.S.
Abstract : Background: Sequence variation at chromosome 9p21.3 accounts for 20% of myocardial infarctions (MIs) in several populations. Whereas the risk conferred by the 9p21.3 locus appears to act independently of traditional risk factors, studies suggest that the association between 9p21.3 and MI is modified by glucose homeostasis and lifestyle. We examined if the 9p21.3 variant rs1333049, along with the previously identified predictor fasting insulin, modifies the preventive effect of bariatric surgery on MI incidence. Methods: rs1333049 was genotyped in 1852 patients treated by bariatric surgery and 1803 controls given usual care in the SOS study (Swedish Obese Subjects). MI incidence was determined using national registers. Median follow-up was 21 years (interquartile range 18–24 years). Results: Overall, 366 MIs occurred during follow-up. Among rs1333049 risk-allele carriers (CC+GC), the incidence of MI was reduced in the surgery group compared with the control group (hazard ratio=0.72 [95% CI, 0.57–0.92], P =0.008). By contrast, noncarriers (GG) showed no significant differences in MI incidence between the treatment groups (hazard ratio=1.28 [0.86–1.90], P =0.227; interaction between treatment and the risk-allele P =0.016). In addition, carriers with higher fasting insulin (above the median [17 mmol/L]) experienced significantly higher MI incidence than carriers with lower fasting insulin (hazard ratio=0.58 [0.42–0.78], P <0.001, interaction P =0.031). Conclusions: In the SOS cohort, patients with the chromosome 9p21.3 rs1333049 risk allele together with high fasting insulin levels benefitted from bariatric surgery in terms of reduced incidence of MI. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT01479452. Abstract : Supplemental Digital Content is available in the text.